2019
DOI: 10.1139/cjc-2018-0408
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of lanthanide-doped TiO2nanoparticles and their photocatalytic activity under visible light

Abstract: Four different lanthanide (Ce, Dy, Lu, and Sm) doped TiO2 mesoporous materials were synthesised using the sol–gel method with titanium (IV) isopropoxide as the precursor. All of the synthesized materials were characterised using different analytical techniques, BET, PXRD, TEM, SEM-EDX, Raman, FTIR, photoluminescence, and UV-DRS spectroscopy. Photocatalytic activity and efficacy of the materials in the degradation of caffeine in aqueous solutions was investigated under visible light illumination. Although all m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The FTIR spectra shown in Figure 2 b–d allowed to demonstrate that, due to doping, the broad band of the TiO 2 semiconductor, shown in the region of 540–900 cm −1 in Figure 2 a, changes drastically. According to the literature, this change can be attributed to the presence of Ln-–O stretching modes of vibrations [ 24 ]. Unresolved bands suggest the existence of uniform stresses in the lattice, which is generally associated with defects in the material structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR spectra shown in Figure 2 b–d allowed to demonstrate that, due to doping, the broad band of the TiO 2 semiconductor, shown in the region of 540–900 cm −1 in Figure 2 a, changes drastically. According to the literature, this change can be attributed to the presence of Ln-–O stretching modes of vibrations [ 24 ]. Unresolved bands suggest the existence of uniform stresses in the lattice, which is generally associated with defects in the material structure.…”
Section: Discussionmentioning
confidence: 99%
“…In order to decrease recombination of the pairs (e − /h + ) and shift the absorption wavelength to the wanted visible region (>λ = 400 nm), several specific surface modifications on TiO 2 have been suggested, including doping with different elements, including lanthanides [ 19 , 20 , 21 , 22 , 23 ]. In fact, lanthanide metal ions (Ln 3+ ) have been employed as TiO 2 dopants in numerous investigations since they can considerably modify the physicochemical properties of this photocatalyst [ 24 ]. Doping of TiO 2 with lanthanide elements can occur through two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In eqn (11), molecular O 2 reacts with the electrons (e − ) in the CB and resulted in O 2 c − . Then, O 2 c − reacts with water molecules to produce cOH radical species, as shown in eqn (12). On the other hand, as shown in eqn (13), the h + can react with H 2 O on the surface of photocatalyst to produce cOH radical species.…”
Section: Metal Oxides In Photocatalytic Degradationmentioning
confidence: 99%
“…His research interest is dealing with the various optoelectrical properties of inorganic semiconductors. materials, 12 meaning that for overcoming environmental pollution, the degradation of harmful and toxic contaminant organic compounds using semiconducting photocatalysts is of great signicance. 13 A semiconducting photocatalyst is a material that is used as a catalyst in photocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the improvement of TiO 2 photocatalytic properties by lanthanide ions (rare earth) has been also reported. Since the 4f electron configuration exhibits absorption in the visible light region, several studies reported the effect of some rare-earth ions like Er 3+ , Sm 3+ , Pr 3+ and Nd 3+ [23][24][25][26], resulting in a redshift of its edge absorption. More recently, N. Nithya et al showed that Nd-doped TiO 2 enhanced the degradation of methylene blue (MB) and Congo red (CR) than pure TiO 2 nanoparticles [27].…”
Section: Introductionmentioning
confidence: 99%